(untitled) (American Journal of Islam and Society, 2001)
This book examines the Islamic revolution of Iran and presents a cultural approach to analyzing the events that resulted in the collapse of the monarchical system and the establishment of the Islamic Republic. The book contains seven chapters. An introductory chapter explores the genealogy of the western narrative of modernity and its dichotomizing representation of non-western cultures and societies. The author poses several questions in an attempt to provide a definition for modernity, and in the process explores the story of Iranian modernity. Is modernity a totalizing ideology grounded in European cultural and moral experience and incapable of understanding other cultures? Or, is it a mode of social and cultural experience of the present that is open to all forms of contemporary experiences and possibilities? These questions are addressed in chapter 1, where Mirsepassi examines the process of development of the concept of modernity in the West. He analyzes some of the writings of such thinkers as Montesquieu, Hegel, Karl Marx, Max Weber, Emmile Durkheim, Marshall Berman, Jurgen Habermas, Anthony Giddens, and more recent works by critics of modernity theories such as Edward Sai’d, Arturo Escobar, and Timothy Mitchell. He demonstrates quite convincingly, how in the western conception of modernity, an "Oriental" other, passive, traditional, and irrational, is contrasted to the modem world of the West. At the depth of the discourse of modernity, he finds a hostility to non-western cultures that excludes them from the possibility of meaningful participation in the making of the modem world. He criticizes the western conception of modernity because it is Euro-centric and denies other cultures a positive role in the making of the modem world. These theories all share the belief that "they are objective, culturally neutral, and universally applicable to all societies." (pp. 6-9) Therefore, the core conception of modernity theory ...